Effect of Tongxinluo on Nephrin Expression via Inhibition of Notch1/Snail Pathway in Diabetic Rats. (31st August 2015) - Cui, Fangqiang; Zou, Dawei; Gao, Yanbin; Zhang, Na; Wang, Jinyang; Xu, Liping; Geng, Jianguo; Li, Jiaoyang; Zhou, Shengnan; Wang, Xinyao
Abstract : Podocyte injury is an important mechanism of diabetic nephropathy (DN). Accumulating evidence suggests that nephrin expression is decreased in podocyte in DN. Moreover, it has been demonstrated that tongxinluo (TXL) can ameliorate renal structure disruption and dysfunction in DN. However, the effect of TXL on podocyte injury in DN and its molecular mechanism is unclear. In order to explore the effect of TXL on podocyte injury and its molecular mechanism in DN, our in vivo and in vitro studies were performed. Our results showed that TXL increased nephrin expression in diabetic rats and in high glucose cultured podocyte. Meanwhile, TXL decreased ICN1 (the intracellular domain of notch), HES1, and snail expression in podocyte in vivo and in vitro. More importantly, we found that TXL protected podocyte from injury in DN. The results demonstrated that TXL inhibited the activation of notch1/snail pathway and increased nephrin expression, which may be a mechanism of protecting effect on podocyte injury in DN.